Real-Time Craters Generation On Dynamic Terrains - Cossetin Neto, Alfredo; Franzin, Flávio; Pozzer, Cesar Tadeu; Berwaldt, Natan; Di Domenico, Gabriel; De Freitas, Gustavo (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2024: Anais do XXIII Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2024.241214, 2024)
This paper presents an innovative technique for simulating crater deformations caused by explosions in large height map-based virtual terrains. Unlike traditional methods, our proposed approach does not directly deform the landscape. Instead, we discretize the crater information into simple variables and store it in a compact GPU-based hash table. The actual deformation is then calculated later using compute shaders each time a block of the height map is loaded to the GPU. This approach allows for the deformation of terrain at very far distances without the need to load large heigh map textures, thereby saving memory, as demonstrated by our comparison with another method. Moreover, this paper explores techniques to enhance the visual quality of craters by incorporating noise algorithms and appropriate coloring, thus increasing the overall realism of the areas affected by explosions.